Therapeutic Potential of α-Synuclein Evolvability for Autosomal Recessive Parkinson’s Disease - Jianshe Wei; Gilbert Ho; Yoshiki Takamatsu; Eliezer Masliah; Makoto Hashimoto (Parkinson's Disease)
The majority of Parkinson’s disease (PD) is sporadic in elderly and is characterized by α-synuclein (αS) aggregation and other alterations involving mitochondria, ubiquitin-proteasome, and autophagy. The remaining are familial PD associated with gene mutations of either autosomal dominant or recessive inheritances. However, the former ones are similar to sporadic PD, and the latter ones are accompanied by impaired mitophagy during the reproductive stage. Since no radical therapies are available for PD, the objective of this paper is to discuss a mechanistic role for amyloidogenic evolvability, a putative physiological function of αS, among PD subtypes, and the potential relevance to therapy. Presumably, αS evolvability might benefit familial PD due to autosomal dominant genes and also sporadic PD during reproduction, which may manifest as neurodegenerative diseases through antagonistic pleiotropy mechanism in aging. Indeed, there are some reports describing that αS prevents apoptosis and mitochondrial alteration under the oxidative stress conditions, notwithstanding myriads of papers on the neuropathology of αS. Importantly, β-synuclein (βS), the nonamyloidogenic homologue of αS, might buffer against evolvability of αS protofibrils associated with neurotoxicity. Finally, it is intriguing to predict that increased αS evolvability through suppression of βS expression might protect against autosomal recessive PD. Collectively, further studies are warranted to better understand αS evolvability in PD pathogenesis, leading to rational therapy development.